ダイ37・38ジ ニホン ナンキョク チイキ カンソクタイ ニオケル ミナミ インドヨウ カイザン チョウサ - 野木, 義史; ノギ, ヨシフミ; 金尾, 政紀; カナオ, マサキ; 神沼, 克伊; カミヌマ, カツタダ; Nogi, Yoshifumi; Kanao, Masaki; Kaminuma, Katsutada (1998)
P(論文) 第37・38次南極地域観測(JARE-37,JARE-38)の航路の南インド洋で海山調査を行い, 砕氷船「しらせ」で現在までに海図に記されていない海山を同定した。1995年12月JARE-37では57°S, 98°E付近の海域で詳しい調査を行い, 56°59.41′S, 98°05.51′Eで海山の最も浅い部分, 水深約983mを記録した。この海山の海平原からの高さは3400m以上, 半径は約20km程度と見積もられる。1996年12月JARE-38では, 60°S, 107°E付近の海域で調査を行い, 二つの海山を同定した。北側の海山で観測された最も浅い水深は1141m, 南側の最も浅い水深は2024mであった。この二つの海山はほぼ北東方向に延びる長さ約35kmの小規模な海山列を形成している。 Surveys of seamounts in the Southern Indian Ocean were carried out during the 37th and 38th Japanese Antarctic Research Expedition (JARE-37 and JARE-38). Previous uncharted seamounts were identified on board the icebreaker SHIRASE. During the JARE-37 cruise in December 1995,the survey was conducted around (57°S, 98°E) and the shallowest depth of a seamount, 983m, was recorded at 56°59.41′S and 98°05.51′E. The height of the seamount above the ocean floor is more than 3400m and its radius is about 20km. During the JARE-38 cruise in December 1996,the survey was conducted around (60°S, 107°E) and two seamounts were found. The shallowest depth of the northern seamount is 1141m and that of the southern seamount is 2024m. These two seamounts form a small seamount chain about 35km long extending in the northeast-southwest direction. departmental bulletin paper